Radiotherapy for breast cancer associated with a cutaneous presentation of systemic mastocytosis—a case report and literature review. Issue 11 (23rd November 2018) - Easwaralingam, Neshanth; Wu, Ying; Cheung, Deborah; Tiver, Ken; Fuller, Stephen; Edirimanne, Senarath
Abstract: Ionizing radiation therapy is a common adjuvant therapy for individuals undergoing surgery for breast cancer. There are many well-recognized acute and chronic cutaneous reactions that can vary in severity, course and duration. We present a rare cutaneous manifestation of systemic mastocystosis, in a 59-year-old female who underwent adjuvant radiotherapy following local excision of ductal carcinoma in situ.